2019
DOI: 10.7759/cureus.5879
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methylphenidate Misuse in Medical Colleges in Pakistan: A Cross-sectional Study

Abstract: ObjectiveTo determine the prevalence of nontherapeutic use of methylphenidate as well as to ascertain any benefits, side effects, and other factors associated with this use.Materials and MethodsA cross-sectional study was conducted in medical colleges in Pakistan using a self-constructed, validated questionnaire. The sample size was calculated using Open Source Statistics for Epidemiological Health software (OpenEpi web-based open-source program, MIT license), and it was determined to be 400. The type of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
0
6
0
13
Order By: Relevance
“…Indeed, the main motivations for misusing methylphenidate may relate to improving concentration (65.2%), helping with studying (59.8%) and increasing wakefulness (47.5%) [ 73 ]. Other studies have associated methylphenidate misuse with the need to help with concentration, stay alert, have more energy and improve self-confidence levels [ 17 , 34 , 70 ]. A 2019 UK qualitative study with Biomedical Science undergraduate students examined their understanding of the risks of non-prescribed drugs, and particularly modafinil, misuse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the main motivations for misusing methylphenidate may relate to improving concentration (65.2%), helping with studying (59.8%) and increasing wakefulness (47.5%) [ 73 ]. Other studies have associated methylphenidate misuse with the need to help with concentration, stay alert, have more energy and improve self-confidence levels [ 17 , 34 , 70 ]. A 2019 UK qualitative study with Biomedical Science undergraduate students examined their understanding of the risks of non-prescribed drugs, and particularly modafinil, misuse.…”
Section: Resultsmentioning
confidence: 99%
“…The past few years have seen increasing levels of concern about the use of pharmaceutical cognitive enhancement among university students worldwide, with the lifetime prevalence of CEs misuse among these subjects ranging from 6% to 20%, depending on the study subject [ 67 ]. Of particular concern, however, is CE’s use in Health Sciences/ Biomedical students [ 34 , 36 , 38 , 39 , 45 , 48 , 54 , 57 , 63 , 67 , 70 , 71 ]. Most data initially emerged from the United States [ 61 , 75 , 113 ], eventually followed by reports from the United Kingdom [ 22 ], Australia [ 46 , 50 ]; and Europe, namely from France [ 53 , 60 ], and Italy [ 38 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a prevalence rate of 3.5% of ADHD was found among medical college students in China, and was associated with suicidality through drinking, smoking and depression [8]. A study from Pakistan revealed that 5.1% of medical students admitted that they had ADHD, despite the fact that the prevalence should be higher according to one concurrent report of methylphenidate use [9]. A similar rate of prevalence was found in Iran (5.4%) [10].…”
Section: Introductionmentioning
confidence: 86%
“…no entanto, obteve relatos de melhor atenção e um maior nível de vigília como alguns impressão de que ela pode ajudar os estudantes a destacarem-se nos seus estudos. No entanto, a abstinência duradoura é uma grande desvantagem e é responsável por desencadear um ciclo vicioso de dependência da droga (JAVED et al, 2019).…”
Section: Efeitos Do Mph No Sistema Nervoso Centralunclassified